Anatomical Variations of Gerdy’s Tubercle: The Distal Attachment Site of the Iliotibial Tract - Asma Siddique, Fariha Qureshi, Hafiz Moeen-Ud-Din, Roomana Hashim, Muhammad Umar, Ayesha Afzal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Morphometric evaluation of Gerdy’s tubercle located on upper end of tibia has very significant role in orthopedics for the treatment and surgeries of total knee replacement. A triangular facet known as Gerdy’s tubercle is located on the lateral tibial condyle. Aim: To analyze and evaluate the variations in size, shape, prominence and localization of Gerdy’s tubercle in dry human tibial bones. Study Design: Cross sectional morphological study Place and Duration of Study: Department of Anatomy, Akhtar Saeed Medical & Dental College Lahore from 1st July 2022 to 31st December 2022. Methodology: To record the variations of Gerdy’s tubercle in this research work, 50 dry human tibial bones were obtained. Morphologically shape and bony prominence of this tubercle was noted. Vernier caliper and ruler were used to measure the diameter and localization of the tubercle. Results: The calculated mean diameter of Gerdy’s tubercle irrespective of the side of tibia was 12.5±2.85mm. This tubercle on tibia was noted as triangular in shape in 60% bones and oval in 30% and irregular in 10%. The surface prominence of Gerdy’s tubercle was observed to be rough in 20%, smooth in 80% of the total bones. For localization of the tubercle, the distance measured between the tibial tuberosity to the Gerdy’s tubercle. It was 54.5±6 mm on all total bones. Conclusion: The present study provides the morphological and morphometrical evaluation of the variations in Gerdy’s tubercle on upper end of tibial bones, furnishing an anatomical correlation of these anatomical information of the tubercle with the orthopedic and radiological manifestations. Keywords: Tibial anterolateral facet, Gerdy’s tubercle, Localization of Gerdy’s tubercle, Anatomical variations